Discovery Learning Model in Elementary Schools (Modification of Model Based on Learning Video Media) - Khairat (Yayasan Zia Salsabila, 2024)
This research aims to determine the improvement in student learning outcomes using a discovery learning model based on video learning media. The type of research is experimental research, namely conducting learning as an effort to improve student learning outcomes in Islamic Religious Education (PAI) learning. The research design used in this research is One Groups Pretest-Posttest Design, namely a research design that includes a pretest before treatment and a posttest after treatment. The results of research related to the use of discovery learning learning models based on learning video media obtained an N-Gain value of 0.73 with a high category with a percentage of 73.00% and the calculated results of the significance level of 0.000 were smaller than the significance of 0.05 (0.000<0.05) which concluded that there was an increase in student PAI learning outcomes after learning using the discovery learning learning model based on video learning media in class V of SD Negeri 104242 Lubuk Pakam, Deli Serdang Regency, Academic Year 2022/2023.